Passivity based-control technique incorporating genetic algorithm for design of a free piston Stirling engine. (March 2019) - Zare, Sh; Tavakolpour-Saleh, A.R.; Binazadeh, T.
Highlights: Design the free piston Stirling engine (FPSE) based on passivity based control. Using GA technique to obtain the design parameters. Validity of the proposed method is shown experimentally. Abstract : In this paper, a novel design philosophy of free piston Stirling engines based on passivity based-control technique incorporating genetic algorithm is presented. First, the design problem of an FPSE is expressed as a physical nonlinear servo control system with unknown parameters. Accordingly, the desired motions of power piston and displacer (i.e. design objectives) are regarded as the reference trajectories of the control loop. Then, the unknown design parameters of the nonlinear control system including cross sectional-area of the displacer rod, mass and spring stiffness of the power piston and displacer, phase difference, hot gas temperature, and control coefficients are found using a GA along with an error-based objective function. Next, the estimated values of unknown parameters are used to simulate the control system performance. Subsequently, the simulated control system response is compared to the desired trajectories. It is found that the simulated displacements and velocities for both pistons as well as the corresponding limit cycles are close to the desired references of the control system. Finally, simulated performance of the FPSE is verified through experimental results. The outcomes of this research clearly reveal the effectiveness of the proposed nonlinear control-based design technique of the free piston Stirling engine (SUTECH-SR-1).